Implementation of Public Service Policy at the Buleleng Resort Police Service Center (SPKT) in Improving Service Quality and Community Trust - Kadek Robin Yohana; I Wayan Sutrisna; Ni Luh Putu Widyantari (PT Publikasiku Academic Solution, 2025)
This research discusses the implementation of public service policies at the Integrated Police Service Center (SPKT) of Buleleng Police aimed at improving service quality and public trust. Using a qualitative descriptive approach with empirical juridical methods, the study involved in-depth interviews with 15 SPKT officers, 3 police administrators, and 25 community members who used SPKT services. Data analysis employed thematic methods to identify patterns in service implementation. Findings reveal that effective public service is vital for building police-community trust. SPKT operates under Chief of Police Regulation No. 23 of 2010, providing administrative services such as receiving reports, issuing driving licenses, and criminal background check certificates (Surat Keterangan Catatan Kepolisian or SKCK). However, challenges remain, including code of ethics violations, limited human resources (8 officers for 150 daily visitors), and high public expectations. To tackle these issues, Buleleng Police introduced innovations like the Antos (Integrated Police Service Center Online Queue) system, which cut average waiting time from 3.5 to 1.2 hours. They also improve personnel competence and integrity through monthly training and encourage technological service innovations. The success of policy implementation depends largely on commitment, integrity, and adaptation to technology. This research aims to guide future development of public service policies within the police to promote good governance.